"Cooking up" pottery recipes: A diachronic technological and provenance analysis of cooking ware ceramics from prehistoric Heraion on Samos, Greece (ca. 4500–1700 BCE). (February 2021) - Menelaou, Sergios; Kouka, Ourania
Highlights: Integrated analysis of cooking pots from Heraion-Samos produced diachronic patterns. Identification of long-lived clay recipes suggests distinct production units. Shared technological practice cross-cut fabric groups. Suggestion of provenance of outlier imports from central and west Aegean. Abstract: This paper, drawing from a broader analytical project on the Chalcolithic, Early and Middle Bronze Age pottery from Heraion on Samos, discusses the diachronic development of cooking ware ceramics from the mid 5th through to the early 2nd millennia BC. The preliminary results of this integrated programme of analysis, employing ceramic petrography as its main technique, are based on fabric and clay composition, in association with typological information, morpho–stylistic observations, SEM analysis, as well as with regard to the local geological background of the island. By examining diachronic choices made in the production of cooking pots, being usually characterised in archaeological scholarship as static and resistant to change, this paper has firmly established the identification of a long–lived ceramic production centre in the East Aegean. Continuity and change of technological practice, and craft organisation are also discussed at the micro–scale level, while contributing to the identification of cooking pot movement in the prehistoric Aegean.